PENGARUH PROFITABILITAS PADA NILAI PERUSAHAAN DENGAN GCG DAN CSR SEBAGAI PEMODERASI - Nurbaeti Putri Hakim; Mekani Vestari (JURNAL ILMIAH EDUNOMIKA, 2022)
This study purpose to provide empirical evidence regarding the effect of profitability on firm value with good corporate governance and corporate social responsibility as moderating variable. The population on this study was companies listed on the Indonesia S tock Exchange in the period 2018-2020 with sample was taken using purposive sampling method and obtained samples of 26 companies. The analysis data used in this study was data regression panel. Tobins’Q was used to assess the firm value. Return on Equity was used to asses profitability. Good Corporate Governance was measured by ASEAN Corporate Governance Scorecard whereas Corporate Social Responsibility was measured by Asian Sustainability Reporting Rating (ASRRAT). The result showed that Good Corporate Governance strengthen the effect of profitability on the firm value, whereas Corporate Social Responsibility is very weak in strengthening the positive relationship between profitability to firm value. Keywords : Profitability, GCG, CSR, Firm Value.